A new xanthid crab, Neoliomera zovoensis sp. nov. (Decapoda, Brachyura), from the Lower Eocene beds of Zovo (Vestenanova, Verona, northeast Italy) - de Angeli, Antonio; Garassino, Alessandro (Geologija, 2020)
A new species of Neoliomera Odhner, 1925, Neoliomera zovoensis sp. nov. from the Lower Eocene (Ypresian) of Zovo (Vestenanova, Verona), which co-occurs with other decapod crustacean species in a richly fossiliferous coral-algal-reef in the Monti Lessini (Verona area, northeast Italy) is herein described.